Collection 1989-1999 FRAC Provence-Alpes-Côte-d'Azur. - Fenzy, Rémy; Francblin, Catherine; Maffesoli, Michel; Mangion, Eric; Massera, Jean-Charles; Mouton, Joseph; Rousseau, Pascal; FRAC Provence-Alpes-Côte d'Azur, Marseille Marseille (ARLES : Actes Sud, 2000)
Absalon ; Agnone, Thierry ; Agofroy, Hélène ; Albrecht, Jürgen ; Alechinsky, Pierre ; Alkema, Tjeerd ; Amer, Ghada ; Andrade, Alain ; Appelt, Dieter ; Autard, Georges ; Avril, Armand ; Baquié, Richard ; Barbier, Gilles ; Barré, Martin ; Bart, Cécile ; Bartolani, Judith ; Bartoloméo, Joël ; Basserode ; Bellissen, Jean ; Bélorgey, Yves ; Ben ; Berdaguer, Christophe ; Bertrand, Jean-Pierre ; Blanc, Jean-Luc ; Blazy, Michel ; Boeno, David ; Borofsky, Jonathan ; Bossut, Etienne ; Boucherot, Marc ; Boudjellouli, Belkacem ; BP ; Broccolichi, Pascal ; Bublex, Alain ; Burkhard, Balthasar ; Bustamante, Jean-Marc ; Cabrita Reis, Pedro ; Caccavale, Giuseppe ; Caillol, Claude ; Calle, Sophie ; Castellas, Denis ; Ceccarelli, Jean-Jacques ; Cercle Ramo Nash ; Charvolen, Max ; Clavère, Frédéric ; Closky, Claude ; Cognée, Philippe ; Colin-Thiébaut, Gérard ; Coplans, John ; Corillon, Patrick ; Coupet, Frédéric ; Cragg, Tony (Anthony) ; Creseveur, Élizabeth ; Deacon, Richard ; Delbès, Jean-Louis ; Demozay, Didier ; Dietman, Erik ; Dolla, Noël ; Dupin, Jérôme ; Duyckaerts, Eric ; Fanchon, Sylvie ; Fauguet, Richard ; Fend, Peter ; Fermariello, Sergio ; Figarella, Dominique ; fordacityC ; Förg, Gunther ; Frize, Bernard ; Giraud, Guy ; Goldin, Nan ; Gomila, Francis ; Gonzalez, Yannick ; Graham, Rodney ; Grand, Toni ; Gronon, Philippe ; Guilleminot, Marie-Ange ; Hirschhorn, Thomas ; Horsfield, Craigie ; Hyber, Fabrice ; Jammes, Louis ; Jézéquel, Claire-Jeanne ; Jitrik, Magdalena ; Joseph, Pierre ; Jouve, Valérie ; Jugnet, Anne Marie ; JukeBox ; Julien, Jacques ; Keller, Art ; Kelley, Mike ; Klemensiewicz, Piotr ; Kusnir, Carlos ; Lafont, Suzanne ; Lenoir, Alexandre ; Lesueur, Natacha ; Lévêque, Claude ; Levi, Renée ; Liddell, Siobhan ; Limone, Guy ; etc.
biog., ind. tent., gr. tent., bibliog. p. 412-454
Frans
boek